Isolasi bakteri asam laktat asal feses bayi dan potensinya dalam menghambat pertumbuhan Escherichia coli - Hasbi, Nurmi; Rosyunita; Rahim, Adelia Riezka; Ayunda, Rahmah Dara; Parwata, Wayan Sulaksmana Sandhi; Farras, Afif; Raihan, Al Fikar; Billah, Muhammad Azim (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Lactic acid bacteria (LAB) play an important role in improving performance and mitigating disease because of their ability to maintain the physiological balance of the gastrointestinal tract and resistance to pathogenic bacteria. LAB is one of the bacteria found in the digestive tract. LAB must be isolated from their hosts to increase their efficiency as probiotic ingredients. This study aims to obtain local isolates of LAB a from baby feces through phenotypic identification and antibacterial test. The sample used in the research was the feces of babies aged 1-6 months that patients from Mataram University Hospital. Isolation was carried out by growing bacteria from feces using the Total Plate Count method on MRSA media plus CaCO3. Phenotypic characterization is morphology test, gram stain and biochemical tests. The results of bacterial isolation obtained 8 isolates of LAB. LAB produced a clear zone in the MRSA media, because these bacteria were able to secrete acid in the MRSA. The results of gram staining show that all isolates are gram positive bacteria. Based on the morphology of LAB had characteristic 6 isolates of cocci and 2 isolates of bacilli. All isolates was able to produce an inhibition zone against E. coli with 3 isolates in the moderate category and 5 isolates in the weak category. The best inhibition zone in the medium category is for cocci-shaped bacteria.The existence of LAB isolates from baby feces can be used as a reference source for further research on probiotics such as other antibacterial test